TINGKAT KECEMASAN ATLET PEMULA RUGBY 7S DALAM MENGAHADAPI PERTANDINGAN - Fajar, Muhammad Kharis; Utomo, Rizki Satrio (Universitas Negeri Surabaya, 2021)
Rugby 7 is a sport with high intensity and strong physical and mental needs to compete. Mental is an aspect that needs to be considered because it affects 50% of the results of the match. Factor is one of the things that affect the mental. This study aims to determine how much anxiety athletes face in the competition. This research uses a quantitative approach with a survey method, and uses a questionnaire as a research instrument. The research subjects in this study were rugby 7s beginner athletes from East Java with a sample of 88 athletes. The results of this study were 6.8% athletes with